Diet analysis by next‐generation sequencing indicates the frequent consumption of introduced plants by the critically endangered red‐headed wood pigeon (Columba janthina nitens) in oceanic island habitats. Issue 12 (19th September 2013) - Ando, Haruko; Setsuko, Suzuki; Horikoshi, Kazuo; Suzuki, Hajime; Umehara, Shoko; Inoue‐Murayama, Miho; Isagi, Yuji
Abstract: Oceanic island ecosystems are vulnerable to the introduction of alien species, and they provide a habitat for many endangered species. Knowing the diet of an endangered animal is important for appropriate nature restoration efforts on oceanic islands because introduced species may be a major component of the diets of some endangered species. DNA barcoding techniques together with next‐generation sequencing may provide more detailed information on animal diets than other traditional methods. We performed a diet analysis using 48 fecal samples from the critically endangered red‐headed wood pigeon that is endemic to the Ogasawara Islands based on chloroplast trn L P6 loop sequences. The frequency of each detected plant taxa was compared with a microhistological analysis of the same sample set. The DNA barcoding approach detected a much larger number of plants than the microhistological analysis. Plants that were difficult to identify by microhistological analysis after being digested in the pigeon stomachs were frequently identified only by DNA barcoding. The results of the barcoding analysis indicated the frequent consumption of introduced species, in addition to several native species, by the red‐headed wood pigeon. The rapid eradication of specific introduced species may reduce the food resources available to this endangered bird; thus, balancing eradication efforts with the restoration of native food plants should be considered. Although some technical problems still exist, the trn L approach to next‐generation sequencing may contribute to a better understanding of oceanic island ecosystems and their conservation. Abstract : We performed diet analysis of critically endangered red‐headed wood pigeon using next‐generation sequencer. The results indicated frequent use of introduced species, not only native species, by the pigeon.